# Solve for x: 21 + 7(3x-3) = 9(3x+3) - 15

### 5 Answers | Add Yours

21 + 7(3x-3) = 9(3x+3) - 15

we will factor 3:

==> 21 + 7*3(x-1) = 9*3(x+1) - 15

Now divide all terms by 3:

==> 7 + 7(x-1) = 9(x+1) - 5

open brackets:

==> 7 + 7x - 7 = 9x + 9 - 5

reduce similar:

==> 7x = 9x + 4

Now combine like terms:

==> -2x = 4

**==> x= -2**

To solve the equation 21 + 7(3x-3) = 9(3x+3) -15 for x:

21 + 7(3x-3) = 9(3x+3) -15

All terms have 3, you can cancel the three,

=> 7 + 7 (x-1) = 3( 3x+3) -5

open the brackets

=> 7 + 7x -7 = 9x +9 -5

More all the terms with x to one side and the numerical terms to the other

=> 7x - 9x = 9 -5

=> -2x = 4

=> x= -2

**Therefore x = -2**

We'll move all terms of the given equality to one side, changing their signs.

21 + 7(3x-3) - 9(3x+3) + 15= 0

Now, we'll remove the brackets:

21 + 21x - 21 - 27x - 27 + 15 = 0

We'll combine and eliminate like terms:

-6x - 12 = 0

We'll subtract 12 both sides:

-6x = 12

We'll divide by -6 both sides:

x =-12/6

**x = -2**

Another way to solve the proble would be to factorize by 21, the left side:

21(1+x-1) = 3(9x+9-5)

We'll divide by 3 both sides:

7x = 9x + 4

We'll subtract 9x both sides:

-2x = 4

We'll divide by -2:

**x = -2**

21 + 7(3x-3) = 9(3x+3) - 15 In order to solve for x you are going to multiply everything in the parentheses by the term outside the parentheses.

21 + 21x -21 = 27x + 27 - 15 Combine like terms on both sides. The 21 on the left side will be cancelled out.

21x = 27x + 12 Subtract 21x from both sides of the equation.

21x -21x = 27x + 12 -21x

0 = 6x + 12 Subtract 12 on both sides.

0 -12 = 6x + 12 -12

-12 = 6x divide 6 on both sides to get x by itself.

-12/ 6 = 6x/ 6

-2 = x Here is your answer.

To solve for x:

21 + 7(3x-3) = 9(3x+3) - 15.

Solution:

This is a simple linear equation in one variable x.

Simplify both sides:

21 +21x -21 = 27x +27 -15.

21x = 27x +12.

Subtract 23x from both sides:

21x-27x = 12

-6x = 12

Divide by -6:

-6x/-6 = 12/-6

x = -2